ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR THE DETERMINATION OF CAFFEINE IN GREEN COFFEE BEANS (COFFEA ARABICA L.) FROM THREE DISTRICTS OF WEST JAVA, INDONESIA BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Saputri, Febrina Amelia; Muchtaridi, Muchtaridi (International Journal of Applied Pharmaceutics, 2018)
Objective: To develop and validate a simple, accurate, and precise HPLC method for the determination of caffeine in green coffee beans (Coffea arabica L.) from three districts of West Java, Indonesia. Methods: The analytical method was conducted using Enduro C-18 (250 x 4.6 mm) column with methanol: water (37: 63) as a mobile phase, the flow rate was 1.0 ml/min, and the detector wavelength was set at 274 nm. The selectivity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, precision, and system suitability testing were evaluated as the parameters of validation. Results: The retention time of caffeine was 6.36 min. % RSD for precision was 0.192. The linearity of the method was obtained using a concentration range of 1-200 ppm with the correlation coefficient of 0.998. The limit of detection was 9 ppm and the limit of quantitation was 28 ppm. The accuracy was in between 90.723%-102.853%. Caffeine levels from Garut, Pangalengan, and Tasikmalaya were 1.454 ± 0.004%, 1.574 ± 0.082%, and 2.280 ± 0.004%. Conclusion: The proposed HPLC method meets the acceptance criteria of validation parameters and can be applied for routine analysis.